Developing an Ecological Risk Assessment to Effectively Manage Marine Resources in Data-Limited Locations: A Case Study for St Helena Sand Extraction - Mynott, Frances; Lonsdale, Jemma-Anne; Stamford, Tammy (Frontiers in Marine Science, 2021)
Maritime states are faced with the challenge of effectively managing their marine spaces to use resources sustainably, maximise economic potential and simultaneously protect their marine environments. Anthropogenic activities, whether in isolation or combination, all have effects on the natural environment. Each of these effects has a footprint in time and space. Assessing the distribution and intensity of human activities and their effects on marine biodiversity, and all other human uses and users is necessary for effective spatial planning, as well as to harmonise conservation with sustainable development. Assessing and managing combined pressures from human activities can be achieved using risk assessment and risk management processes. There are multiple examples of environmental risk assessments which propose a similar formula. However, standardised approaches to ecological risk assessment in data-limited locations that relate to sand extraction are limited. Also most assessments require a certain level of information to produce meaningful outcomes, that enable subsequent management action to appropriately reflect the identified level of risk. Here we outline an approach to assess the risk to the marine environment of sand extraction activity within the Exclusive Economic Zone and Marine Protected Area of St Helena Island in the Atlantic. The proposed risk assessment tool has supported the development of a sand extraction management strategy on St Helena, and will be used to inform future management plans and policies that allow anthropogenic activities to take place in a way that balances local management, monitoring and enforcement capability, in line with the International Union for Conservation of Nature (IUCN) Category VI designation. Both the tool and strategy promote sustainable use of resources and protection of the marine environment, which are key objectives stated in the St Helena Marine Management Plan.